Évaluation des réactions post-traumatiques chez les migrants : une étude transculturelle en France et au Brésil - Brunnet, Alice Einloft (2020)
Introduction: This research aimed to investigate the post-traumatic reactions in migrants who live in France and Brazil. Through five studies, diverse aspects of this phenomenon were studied: (1) psychological assessment in a transcultural situation, (2) the validity of the factorial models for Posttraumatic Stress Disorder (PTSD) in a multicultural sample, (3) the factors associated with the development of PTSD, symptoms of anxiety, depression, (4) the post-traumatic growth (PTG), (5) the migration experience. Method: Our total sample consisted of 244 participants, 100 living in France and 144 in Brazil. Participants completed questionnaires assessing symptoms of PTSD, anxiety, depression, and PTG. In addition, a qualitative study was conducted with thirteen participants (5 in France and 6 in Brazil), who responded a semi-structured interview about their migratory experiences. The data were collected in non-governmental organizations that provide support for migrants in both countries. Quantitative data were analyzed using software R. Descriptive analysis, confirmatory factor analysis and path analysis were performed. Qualitative data were analyzed with a thematic analysis on ATLAS.TI software. Results: The results of this thesis are presented in two parts. The first part, called “psychological assessment in transcultural situation”, consists of two articles, one theoretical and one quantitative. The second part, “Migrations and mental health in France and Brazil” consists of two quantitative and one qualitative article. Regarding the factorial structure of PTSD, the tested models presented a good fit to the data, with the ICD-11 model being superior to the DSM-5 model and to the theoretical model “Anhedonia”. Participants in France had higher rates of PTSD, anxiety and depression while respondents in Brazil presented higher rates of PTG. The number of post-migratory stressors was the most important predictor of the mental health outcomes in both countries. Little access to food and feelings of loneliness were negatively associated with PTG. Concerns about the family in the country of origin was a positive predictor. Qualitative results were analyzed from three major categories of the migratory experience: before, during and after migration. Conclusion: Although the models proposed by international manuals are valid in a multicultural sample, clinicians who come in contact with this population must be sensitive to other presentations of the disorder, which can be influenced by cultural issues or by the type of trauma experienced. Our results also show the importance of the host country context in the mental health of migrants, as well as the traumatic events experienced before and after migration